Thermal equation of state of the main minerals of eclogite: Constraining the density evolution of eclogite during the delamination process in Tibet - Z. Ye; Z. Ye; D. Fan; B. Li; Q. Tang; J. Xu; D. Zhang; W. Zhou (Solid Earth, 2022)
Tibet, which is characterized by collisional orogens, has undergone the process of delamination or convective removal. The lower crust and mantle lithosphere appear to have been removed through delamination during orogenic development. Numerical and analog experiments demonstrate that the metamorphic eclogitized oceanic subduction slab or lower crust may promote gravitational instability due to increased density. The eclogitized oceanic subduction slab or crustal root is believed to be denser than the underlying mantle and tends to sink. However, the density of eclogite under high-pressure and high-temperature conditions as well as density differences from the surrounding mantle are not preciously constrained. Here, we offer new insights into the derivation of eclogite density with a single experiment to constrain delamination in Tibet. Using in situ synchrotron X-ray diffraction combined with a diamond anvil cell, experiments focused on minerals (garnet, omphacite, and epidote) of eclogite are conducted under simultaneous high-pressure and high-temperature conditions, which avoids systematic errors. Fitting the pressure–temperature–volume data with the third-order Birch–Murnaghan equation of state, the thermal equation of state (EoS) parameters, including the bulk modulus (KT0), its pressure derivative (<msubsup>KT0′</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="19pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="822100c37246c4995e15e4c9c3a54e05"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-13-745-2022-ie00001.svg" width="19pt" height="15pt" src="se-13-745-2022-ie00001.png"/></svg:svg>), and the thermal expansion coefficient (α0), are derived. The densities of rock-forming minerals and eclogite are modeled along with the geotherms of two types of delamination. The delamination processes of subduction slab break-off and the removal of the eclogitized lower crust in Tibet are discussed. The Tibetan eclogite, which contains 40 vol %–60 vol % garnet and 44 %–70 % eclogitization, can promote the delamination of slab break-off in Tibet. Our results indicate that eclogite is a major controlling factor in the initiation of delamination. A high abundance of garnet, a high Fe content, and a high degree of eclogitization are more conducive to instigating the delamination.